Primary and Secondary School Teachers as Reading Role Models: n Analysis of Reading Habits - Ograjšek, Sabina; Haramija, Dragica (Bralni vzori 2, 2025)
This paper examines the reading habits of primary and secondary school teachers and was conducted within the framework of the project “Reading Role Models: Reading Habits of Professionals in Kindergartens, Schools, Faculties, and Libraries,” which investigates the reading practices of preschool, primary and secondary school teachers, university teachers in pedagogical fields, students in pedagogical programs, and librarians in both school and public libraries. We focused on five questions related to the reading behavior of primary and secondary school teachers: (1) the amount of time they allocate weekly to reading books; (2) the number of books they have read in the past twelve months; (3) reading frequency according to purpose; (4) the types of printed materials they read; and (5) whether they perceive themselves as readers. Some data were also compared with findings from other studies (e.g., Books and Readers VII). We find that Slovenian primary and secondary school teachers generally exhibit a high level of reading engagement, exceeding the average observed in the general population, and that the majority perceive themselves as readers, thereby providing a solid foundation for their role as reading role models.